Preemptive endoluminal vacuum therapy with the VACStent—A pilot study to reduce anastomotic leakage after Ivor Lewis hybrid esophagectomy - Lange, Jonas; Eisenberger, Claus Ferdinand; Knievel, Judith; Linderer, Anne; Heiss, Markus Maria (Frontiers in Surgery, 2023)
Endoscopic treatment by vacuum therapy (EVT) or covered stents has emerged as an improved treatment option for upper gastrointestinal wall defects and is regarded as an improved treatment option for anastomotic leakage (AL) after esophagectomy. However, endoluminal EVT devices may lead to obstruction of the GI tract; and a high rate of migration and missing functional drainage has been shown for covered stents. The recently developed VACStent, a combination of a fully covered stent within a polyurethane-sponge cylinder may overcome these issues allowing EVT while stent passage is still open. Initial clinical applications have demonstrated efficacy, practicability and safety in the treatment of esophageal leaks (AL). In this pilot study, 9 patients after neoadjuvant therapy undergoing hybrid esophagectomy received the VACStent in a preemptive setting for the assessment of the reduction of the AL rate, postoperative morbidity and mortality. Technical success of the application of the VACStent® was achieved in all interventions. One patient experienced anastomotic leakage 10 days after esophagectomy and was successfully treated with two consecutive VACStents and a VAC Sponge. In summary, mortality in-hospital was 0% and anastomotic healing was uneventful without septic episodes. No severe device-related adverse events (SADE) nor significant local bleeding or erosion could be observed. Oral intake of liquids or food was documented in all patients. The device handling was regarded uncomplicated. The preemptive application of the VACStent offers a promising new option for improved clinical treatment avoiding of critical situations in hybrid esophagectomy, which should be validated in a large clinical study.